Firm value and stock price volatility: The moderating role of esg performance - Primacintya, Vincentia Anindha; Novelia Emma Angelina; Syalom Tri Putra; Bagas Samuel Christiananta (Jurnal Akuntansi dan Manajemen, 2026)
This study aims to explore the impact of firm value on stock price volatility and the role of ESG performance in moderating this relationship. Using data from non-financial companies listed on the Indonesia Stock Exchange for the period 2014-2023, this study employs a quantitative research approach with Generalized Least Square (GLS) testing. The hypothesis testing method used is regression analysis using Stata17. The study revealed a negative and significant correlation between firm value and stock price volatility, indicating that higher firm value is associated with lower stock price volatility. Additionally, the findings suggested that ESG performance strengthens the relationship between firm value and stock price volatility. The study concludes that improving ESG performance leads to a better corporate reputation, which in turn leads to lower stock price volatility. This research contributes to the existing ESG literature and provides valuable insights for management, regulators, investors, and other stakeholders involved with companies.